Evaluasi BIMTEK Program Pengembangan Keprofesian Berkelanjutan (PKB) Guru Bahasa Inggris Madrasah Aliyah di Kota Tasikmalaya - Rahmatul Fajri, Laili (Program Studi Manajemen Pendidikan Islam, 2024)
Continuous Professional Development (PKB) as part of the Madrasah Education Quality Reform (MEQR) project has a strategic position in strengthening teacher competence. This PKB technical guidance model uses a cascade model. TIN (National Core Team) mentors Provincial Facilitators, then Provincial Facilitators mentor Local Facilitators. In the next cycle, local facilitators guide subject teacher meetings (MGMP). The implementation of PKB is carried out starting from the planning, implementation, and evaluation stages of the program so that its success can be measured. This study aims to describe the analysis of the implementation of the evaluation of BIMTEK PKB in English MGMP Tasikmalaya City using the Kirkpatrick model at levels 1 and 2. The informants in this study were teachers who were registered as participants of BIMTEK PKB MGMP English. Data processing for both levels used Kirkpatrick's weighting formula. The results showed that the participants' satisfaction level ranged from 77-83%. The average pre-test score was 46.58%, while the average post-test score was 58.50%.Keywords: BIMTEK PKB, Training evaluation, Kirkpatrick mode